Working on the Web & Worm: Online Scientific Communities, 1991 - present - Singh, Deepak Sona (2016)
This paper attempts to take a historical approach to look at the changes that scientific communities face over the Internet. It argues that technological development and the changing perceptions over the meanings surrounding the Internet have led to wider participation in generating, preserving and collaboration of scientific knowledge over the Internet. This paper investigates 2 particular case studies from 1991 to 1995 and 2007 to present. These 2 case studies seemingly do not have any links present between them. But this paper will attempt to uncover the intangible links that exist between both of these scientific communities. In doing so, it will account for the rise of citizen scientists who are empowered through the phenomenon of crowdsourcing and crowdfunding to solve scientific problems that these online scientific communities in question are looking to answer. This trend of the discipline of Science becoming more inclusive over the online network raises questions about the emergence of Science 2.0 and its effects on the world.